Antibacterial Activity of Silver Nanoparticles Synthesized by Aqueous Extract of Carthamus oxycantha M.Bieb. Against Antibiotics Resistant Bacteria (Baghdad Science Journal, 2022)
Antibiotics resistant bacteria have become a global problem as a result of the unprogrammed use of antibiotics, resulting in bacterial strains resistant to many antibiotics, or to all available antibiotics. Plants are a good source of primary and secondary metabolites that have a major role in reducing silver nitrate to silver nanoparticles (AgNPs). The production of these nanoparticles were carried out by using aqueous extract of Carthamus oxycantha M.Bieb. This can be verified by color change of the reaction solution from yellow to dark brown because of the excitation of the surface plasmon resonance. AgNPs were characterized by UV-Vis spectroscopy, where they recorded the peak at 420 nm. Fourier Transformation-infrared (FTIR) was conducted to identify the effective plant group that contributes to the formation of AgNPs and it was found that proteins and phenols have the major role in the formation of those nanoparticles. Shapes and sizes of the synthesized AgNPs were characterized by Scanning Electron Microscope (SEM) with a range of 50-80nm in size and spherical in shapes. Antibacterial activity of AgNPs were tested against Multi-Drug Resistant bacteria (MDR), Extremely antibiotics Resistant (XDR), and Pan drug-resistant (PAN) bacteria, was done in concentrations ranging from 1000-63 µg/ml. The results showed that there were significant variations between the concentrations, the tested bacteria also showed significant differences in its sensitivity to AgNPs. The results recorded a proportional relation between the type of bacterial resistance to antibiotics and it's resistant to AgNPs, therefore the most resistant bacteria to AgNPs in this study Enterobacter cloacae EN2 was resistant to all antibiotics (PAN), while Escherichia coli E11 recorded was the most sensitive bacteria to AgNPs and its resistant only to 3 antibiotics.unprogrammed use of antibiotics, resulting in bacterial strains resistant to manyantibiotics, or to all available antibiotics. Plants are a good source of primary andsecondary metabolites that have a major role in reducing silver nitrate to silvernanoparticles (AgNPs). The production of these nanoparticles were carried out by usingaqueous extract of Carthamus oxycantha M.Bieb. This can be verified by color changedof the reaction solution from yellow to dark brown because of the excitation of thesurface plasmon resonance. AgNPs were characterized by UV-Vis spectroscopy, whererecorded peak at 425 nm. Fourier Transformation-infrared (FTIR) was conducted toidentify the effective plant group that contributes to the formation of AgNPS and it wasfound that proteins and phenols have the major role in the formation of thosenanoparticles. Shapes and sizes of synthesized AgNPs were characterized by ScanningElectron Microscope (SEM) with a range of 50-80nm in size and spherical in shapes.Antibacterial activity of AgNPs were tested against Multi-Drug Resistant bacteria(MDR), Extremely antibiotics Resistant (XDR), and Pandrug-resistant (PAN) bacteria,was done in concentrations ranging from 1000-63 µg/ml. The result showed that theconcentrations from 1000-125 µg/ml inhibited all tested bacterial strains except the S1strain